Telemedicine as an approach to the mental health of healthcare workers in Angola - Serra, Edmilson (2025)
Introduction: African healthcare professionals face significant mental health challenges; therefore, telemedicine can overcome geographical barriers and improve access to mental healthcare. Objective: The objective of this study was to identify the key factors influencing the adoption of telemedicine as a tool to support healthcare workers’ mental health in an Angolan healthcare network and develop a telemedicine model tailored to this context. Methodology: This mixed-method study collected quantitative data from a questionnaire applied to healthcare workers (n = 275), which were analyzed using descriptive statistics and logistic regressions. Qualitative data were obtained through structured interviews (n = 5) with psychologists and psychiatrists, and analyzed using thematic analysis in MAXQDA (Version 2022, VERBI Software, Germany), to identify recurring patterns and themes. The data were triangulated to ensure the rigor and consistency of the findings. Participation was anonymous and voluntary, and informed consent was obtained from all participants. Results: Previous experiences with mental health consultations, perceptions of teleconsultations, and doctor–patient relationship were significant in influencing telemedicine adoption by workers. The thematic analysis revealed four themes: perception and ease of telemedicine use, intention to use, and the perception of mental health in Angola. The key adoption factors for providers included project feasibility, management support, training, payment policies, and adherence to legal, ethical, and deontological standards. Conclusions: The adoption of telemedicine for occupational mental health requires culturally adapted interventions and compliance with technological and data protection standards. Hospital management must address infrastructure challenges and mental health perceptions, and implement sustainable strategies that promote occupational well-being within the organization.